PEG 400-Based Phase Change Materials Nano-Enhanced with Functionalized Graphene Nanoplatelets - Marco A. Marcos; David Cabaleiro; María J. G. Guimarey; María J. P. Comuñas; Laura Fedele; Josefa Fernández; Luis Lugo (Nanomaterials, 2017)
This study presents new Nano-enhanced Phase Change Materials, NePCMs, formulated as dispersions of functionalized graphene nanoplatelets in a poly(ethylene glycol) with a mass-average molecular mass of 400 g·mol−1 for possible use in Thermal Energy Storage. Morphology, functionalization, purity, molecular mass and thermal stability of the graphene nanomaterial and/or the poly(ethylene glycol) were characterized. Design parameters of NePCMs were defined on the basis of a temporal stability study of nanoplatelet dispersions using dynamic light scattering. Influence of graphene loading on solid-liquid phase change transition temperature, latent heat of fusion, isobaric heat capacity, thermal conductivity, density, isobaric thermal expansivity, thermal diffusivity and dynamic viscosity were also investigated for designed dispersions. Graphene nanoplatelet loading leads to thermal conductivity enhancements up to 23% while the crystallization temperature reduces up to in 4 K. Finally, the heat storage capacities of base fluid and new designed NePCMs were examined by means of the thermophysical properties through Stefan and Rayleigh numbers. Functionalized graphene nanoplatelets leads to a slight increase in the Stefan number.